Teor de lactose e caracterização físico-química de queijo de massa lavada durante a maturação - Silva, Franceline Iaguczeski da (2019)
Lactose intolerance is a disorder that affects a large part of the population. In this sense, it becomes feasible the study of manufacturing techniques that make it possible to guarantee the elaboration of products with low lactose content. Taking this into account, the present study aimed to evaluate the lactose content and physical-chemical characteristics of washed mass cheeses during the maturation period. The production of cheese used pasteurized whole milk with a lactose content of 4.55 g/100 g followed by of the curd with 10% hot water at 75 ° C. Lactose content (IC-EC), acidity, pH, water activity, moisture, fixed mineral residue and chlorides were analyzed at 0, 7, 15, 30 and 60 days of maturation. Lactic acid bacteria count was performed. The lactose content obtained at 0 days of maturation was lower than 0.005 g/ 100g, the pH of the cheeses varied from 5,64 ± 0.02 to 6.26 ± 0.10, the acidity found was 0.14 ± 0.00 to 0.22 ± 0.02 during the maturation period, the water activity found was 0.929 ± 0.00 to 0.909 ± 0.01. Lactic acid bacteria count ranged from 5.86 to 7.45 log CFU/g. Therefore, the results showed that the technology used to make these cheeses, using the hot water washing procedure, the type of starter culture used contributed to the low lactose content in the cheeses. These results demonstrate a great alternative for small business and industrial scale production of naturally lactose-free cheeses, adding new options in the milk derivatives market to intolerant consumers.